ANSIEDADE, DEPRESSÃO E ESTRESSE EM MULHERES COM DOR PÉLVICA CRÔNICA - Aragão, Mariana Serra de (2011)
The Chronic Pelvic Pain (CPP) has been defined as pain in the pelvic region, non-cyclic, with duration of 6 months. Women with CPP may have levels of anxiety, depression and stress. Objective: To identify the prevalence of depression, anxiety and stress in women from the general community of St. Louis with chronic pelvic pain and verify their possible association with the duration and intensity of pain. Methods: Case-control study, which included 54 women with chronic pelvic pain, making the case group, and 150 women in the control group. The instruments used for data collection were Anxiety Inventory and the Beck Depression Inventory and the Stress Symptoms for Adults LIPP. Among the variables used are: time in months of pain and signs and symptoms of anxiety, depression and stress. Results: The prevalence in the case of stress was 59.26%, while anxiety and depression in both minimum level, was 35.19% and 50%, respectively. At level severe depression and anxiety were present in 3.70% and 11.11%, respectively. In the control group, 36% had stress. In the same group, at a minimum, anxiety occurred in 67.33% and 78.67% in depression. In severe level prevalence was 3.33% and 1.33% for anxiety and depression, respectively. There was a positive correlation (r = 0.1275) between pain intensity and depression. Conclusion: Women with CPP have higher scores for anxiety, depression and stress compared to women without CPP, depression being positively correlated with pain intensity.